Comparison of physical, chemical, physico-chemical, and enzymatic pretreatment of paddy straw for ethanol production - Sudarshan Sahu; Urbi Bansal; Gursharan Singh; Shailendra Kumar Arya (Sustainable Chemistry for the Environment)
The global shift towards renewable energy has heightened the importance of bioethanol as a sustainable alternative to fossil fuels, addressing environmental concerns and reducing greenhouse gas emissions. Sustainable chemistry offers innovative solutions for converting agricultural residues into valuable biofuels, yet challenges in optimizing pretreatment and enzymatic processes persist. This study addresses these gaps by systematically comparing physical, chemical, physicochemical, and enzymatic pretreatments to enhance ethanol yields from paddy straw. Methods included alkali, sonication, and alkali-assisted sonication treatments to modify substrate composition, followed by enzymatic hydrolysis using cellulase, xylanase, and mannanase. Results revealed that alkali-assisted sonication yielded the highest reducing sugar concentrations (30 ± 0.8 mg/mL) and ethanol productivity (0.41 g/L/h), with a saccharification percentage of 89 % and ethanol yield of 0.58 g/L. In contrast, xylanase exhibited a saccharification percentage of 83 % with an ethanol productivity of 0.28 g/L/h, while cellulase achieved 85 % saccharification and 0.35 g/L/h ethanol productivity. Mannanase showed the lowest performance with 79 % saccharification and 0.21 g/L/h ethanol productivity. A synergistic enzyme cocktail maximized substrate breakdown and sugar release. This research underscores the critical role of pretreatment and enzyme selection in advancing bioethanol production, offering a sustainable pathway to valorize agricultural waste into clean energy.